2021
DOI: 10.1038/s41598-021-91172-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis and beneficiary identification of adjuvant external beam radiotherapy for stage pT4b sigmoid colon cancer

Abstract: The clinical efficacy of adjuvant radiotherapy in sigmoid colon cancer remains questioned. To evaluate the clinical efficacy of adjuvant external beam radiotherapy (EBRT) for patients with pathologic stage T4b sigmoid colon cancer. Patients with stage pT4b sigmoid colon cancer receiving adjuvant EBRT or not followed by surgery between 2004 and 2016 were extracted from the Surveillance, Epidemiology, and End Results database. Analysis of overall survival (OS) was performed using Kaplan–Meier curves and prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These findings have also been confirmed by other studies [ 12 , 44 ]. Previously, we also found that some sigmoid colon cancer patients may benefit from postoperative RT [ 17 ], and this study once again demonstrated the positive effect of adjuvant RT on survival from the perspective of locoregional recurrence.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These findings have also been confirmed by other studies [ 12 , 44 ]. Previously, we also found that some sigmoid colon cancer patients may benefit from postoperative RT [ 17 ], and this study once again demonstrated the positive effect of adjuvant RT on survival from the perspective of locoregional recurrence.…”
Section: Discussionsupporting
confidence: 72%
“…Using SEER*Stat 8.3.8 (IMS, Inc. USA. https://seer.cancer.gov/seerstat/ ), cases were identified based on the third edition of the International Classification of Diseases for Oncology code, as described in a previous article [ 17 ]. The screening process is illustrated in Additional file 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor differentiation was divided into three groups: well/moderately differentiated, poorly differentiated/undifferentiated, and unknown. Tumor size was classified into three categories: < 5 cm, ≥ 5 cm, and unknown 11 , 12 . Serum carcinoembryonic antigen (CEA) status was classified into three categories: elevated, normal, and unknown.…”
Section: Methodsmentioning
confidence: 99%
“…Recent global cancer statistics have shown that the incidence of colorectal cancer has risen to the third highest, with the mortality rate ranking second, and the number of newly diagnosed cases ranking fifth (1). Currently, adjuvant chemotherapy following curative surgery remains the preferred curative treatment for colorectal cancer (2). However, due to population aging and urban industrialization, the incidence and mortality rates of colorectal cancer have significantly increased (3).…”
Section: Introductionmentioning
confidence: 99%